Petroleum Wastewater Purification by Biomass Adsorption: Dynamics and Performance of a Fixed Bed Column - Elba Gomes dos Santos; Odelsia L. Sánchez de Alsina; Flávio L. Honorato da Silva (Adsorption Science & Technology)
The effect of operational variables on the adsorption of organic pollutants in a fixed bed of biomass was studied. Dispersions of commercial gasoline in water were used as synthetic effluents to simulate petroleum effluent contaminated by organic products. Coconut mesocarp and sugar cane bagasse in the natural form were used as biomass adsorbents. The influence of input gasoline concentration, operational flow rate and fixed bed depth of biomass on the dynamic behaviour of the fixed bed column was investigated. The bed performance was evaluated by means of a 2 3 factorial design plus star configuration with three experiments in the central point and the average exit gasoline concentration as the response variable. In general, the coconut mesocarp gave better results than the sugarcane bagasse. Depending on the operational conditions, it was possible to obtain effluents which were virtually free from organic contaminants.